Volumetric MRI-Based Biomarkers in Huntington's Disease: An Evidentiary Review - Kinnunen, Kirsi M.; Schwarz, Adam J.; Turner, Emily C.; Pustina, Dorian; Gantman, Emily C.; Gordon, Mark F.; Joules, Richard; Mullin, Ariana P.; Scahill, Rachael I.; Georgiou-Karistianis, Nellie; , The Huntington's Disease Regulatory Science Consortium (HD-RSC); Aggarwal, Varun; et al. (Frontiers in Neurology, 2021)
Huntington's disease (HD) is an autosomal-dominant inherited neurodegenerative disorder that is caused by expansion of a CAG-repeat tract in the huntingtin gene and characterized by motor impairment, cognitive decline, and neuropsychiatric disturbances. Neuropathological studies show that disease progression follows a characteristic pattern of brain atrophy, beginning in the basal ganglia structures. The HD Regulatory Science Consortium (HD-RSC) brings together diverse stakeholders in the HD community—biopharmaceutical industry, academia, nonprofit, and patient advocacy organizations—to define and address regulatory needs to accelerate HD therapeutic development. Here, the Biomarker Working Group of the HD-RSC summarizes the cross-sectional evidence indicating that regional brain volumes, as measured by volumetric magnetic resonance imaging, are reduced in HD and are correlated with disease characteristics. We also evaluate the relationship between imaging measures and clinical change, their longitudinal change characteristics, and within-individual longitudinal associations of imaging with disease progression. This analysis will be valuable in assessing pharmacodynamics in clinical trials and supporting clinical outcome assessments to evaluate treatment effects on neurodegeneration.